Simulasi Peningkatan Keekonomian Pembangkit Listrik Hibrida Sebagai Demand Response Ketenagalistrikan di Provinsi Riau - Dalimunthe, Yuliandi Hidayat (Jurnal Pendidikan Indonesia, 2025)
Riau Province continues to face a power supply deficit, requiring a reliable and sustainable strategy. This study aims to improve power-system economics through a demand-response scheme. A quantitative approach is employed via techno-economic simulations, comparing a baseline gas-turbine (PLTG) scenario with a hybrid system integrating 930 MWp PV, 416 MWh BESS, and a Smart Substation over a 25-year horizon. Results indicate a Net Present Value (NPV) of USD 66,973,254.74, an Internal Rate of Return (IRR) of 10.03%, a Payback Period at about year 7 month 7, and a Discounted payback at about 14 years 3 months. For the PV component, the LCOE is USD 0.03836/kWh. These findings confirm that the PV–BESS–Smart Substation configuration is financially and operationally viable as a demand-response option that enhances cost efficiency and system reliability in deficit areas, while supporting the energy transition toward Net Zero Emission and informing regional energy planning and national electricity policy.